以協同合作模式建構研究者知識之研究 A Study of Using Collaborative Mode to Construct Researcher Knowledge - Jiann-Cherng Shieh; Chia-Tien Wu (Jiàoyù zīliào yǔ túshūguǎn xué, 2010)
研究者初次欲進入一個領域進行知識探索與研究時,最常遭遇的困難是研究者不知道該領域知識有哪些,比如領域知識的主題概念、使用詞彙等。即便在資訊傳遞發達的今天,在無明確搜尋目標與模糊關鍵詞語情況下,研究者利用搜尋引擎想要在有限的時間找尋到正確需要的資訊是非常困難的。對此問題人們最直接的反應就是詢問有經驗的研究者,但誰是你的有經驗研究者呢?研究者亦往往無法找到合適的人選,來解答自己的疑問。為解決上述研究者在初踏入新的研究領域進行知識探索與研究時所遇到的困境,本研究欲提出「以協同合作的模式讓研究者共同創造趕鴗漯漯壅悀漁e並建構領域的知識結構」的概念與機制,以保存研究領域的知識,提供研究者方便查詢、瀏覽領域知識結構,相互分享知識經驗,順利完成自身的研究。本研究以資訊架構領域作為建構領域知識結構的實例,讓資訊架構領域的研究者透過Wiki協作平台做為知識分享的環境,研究者可以在平台上進行文獻閱讀心得分享、主題知識共筆撰寫、參考文獻關連引用等知識分享。除此之外,研究者所分享之知識內容與註記之概念關鍵字,經過整理與分析可成為知識組織與分類的元素之後,再透過各關鍵字語意關係之界定,描述知識概念間之連結,並以主題地圖的技術建構資訊架構領域之知識結構,以做為研究者更完整便利之參考。 Whenever the researcher took his first step into some academic field to explore knowledge and do research, most difficult experience is that he did not know what domain knowledge, such as its subject concepts, glossary, does have. Even in today with well developed information transmission, it is very difficult to find out his required information correctly by search engines without definite targets and keywords in limited time. What most immediate response is to inquire the experienced researchers this question. But who are your experienced researchers? The researcher himself was also unable to find the appropriate candidates. In order to resolve the problem, this research proposes the concept and mechanism of collaborative mode to let researchers jointly create domain knowledge and corresponding knowledge structure. The purpose is to preserve their research knowledge and facilitate researchers to inquiry, browse the domain knowledge structure and share their research experiences to complete their own work smoothly. This research takes the domain of information architecture as a study case for constructing knowledge structure. Sharing knowledge on the Wiki collaborative platform, researchers can share what they are reading, write subject knowledge with others, quote reference correlations, etc. Additionally, the knowledge contents and marked concept keywords that researchers shared, can be reorganized and analyzed, and then may become the elements of knowledge construction and classification. After defining semantic relations of keywords and describing linkages between knowledge concepts, we apply the technology of subject map to construct the knowledge structure of the information architecture domain. The resulted structure will facilitate researchers to accomplish their research work completely and conveniently.